2018
DOI: 10.24203/ajas.v6i6.5583
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Construction Companies in Southeast Asia using Static and Dynamic Panel Data

Abstract: Global competition has challenged the performance of construction companies in Southeast Asia. This research determines factors that influence the performance of construction companies.  Data collections were obtained from stock exchanges of countries under the study from years 2013 to 2016. The research methods use static and dynamic panel data. The results reveal that financial performance of construction companies is affected by DER, interest rate and efficiency, while their market performance is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Table 1. Profit rate and risk in ASEAN counties in 2016 [4]. 1 above, it can be concluded that Indonesia presents the highest risk in the construction industry while Singapore presents of that of the lowest risk in the construction industry.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Table 1. Profit rate and risk in ASEAN counties in 2016 [4]. 1 above, it can be concluded that Indonesia presents the highest risk in the construction industry while Singapore presents of that of the lowest risk in the construction industry.…”
Section: Introductionmentioning
confidence: 92%
“…The construction industry in Southeast Asian countries, especially the Association of Southeast Asian Nations (ASEAN), attracts substantial attention and investment due to the industry's high return value. For example, the construction sector in Indonesia is recognized as the largest in the ASEAN region and ranks fourth globally [4]. In the fiscal year of 2014, Indonesia's construction industry contributed approximately USD 267 billion, surpassing other ASEAN countries, including Thailand (USD 33 billion), Malaysia (USD 32 billion), the Philippines (USD 25 billion), Singapore (USD 24 billion), and Vietnam (USD 16 billion) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation